2019
DOI: 10.1111/apa.14957
|View full text |Cite
|
Sign up to set email alerts
|

Conjugate vaccines dramatically reshaped the epidemiology of bacterial meningitis in a well‐defined child population

Abstract: AimWe explored the impact of vaccination on bacterial meningitis in a well‐defined population of children on the island of Crete, Greece, over a 27‐y period.MethodsThis was a retrospective observational study of all mandatory notifications of bacterial meningitis in patients aged 1 mo‐14 y from 1991 to 2017.ResultsThere were 245 patients with proven (n = 227) or suspected (n = 18) bacterial meningitis, and eight deaths were recorded, giving a case fatality rate of 3.3%. The mean annual incidence rate (IR) per … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…In Greece, prior to 2000, a much larger proportion of cases were due to serogroup C, with a peak in the late 1990s. 14 While the number of cases were already declining in Greece, the introduction of MenC vaccination in 2001 has been proposed to account for the greatly reduced incidence of cases since that time, 14 , 15 with less than seven cases per year attributed to serogroup C in the period 2010 to 2020. Furthermore, the introduction of the MenACWY vaccine to Greece in 2012 led to the reduced incidence of serogroups W and Y compared with the high incidence experienced by Western European countries between 2013 and 2017.…”
Section: Discussionmentioning
confidence: 99%
“…In Greece, prior to 2000, a much larger proportion of cases were due to serogroup C, with a peak in the late 1990s. 14 While the number of cases were already declining in Greece, the introduction of MenC vaccination in 2001 has been proposed to account for the greatly reduced incidence of cases since that time, 14 , 15 with less than seven cases per year attributed to serogroup C in the period 2010 to 2020. Furthermore, the introduction of the MenACWY vaccine to Greece in 2012 led to the reduced incidence of serogroups W and Y compared with the high incidence experienced by Western European countries between 2013 and 2017.…”
Section: Discussionmentioning
confidence: 99%
“…Introduction of the Haemophilus influenzae type B and Streptococcus pneumoniae vaccines has led to a dramatic reduction in childhood bacterial meningitis. 42 The most recent AAP guideline on the topic does not recommend the routine performance of a lumbar puncture on all children with a simple febrile seizure. 2 Rather, the guideline presents lumbar puncture as an option in children between 6 and 12 months of age whose immunization status for Haemophilus influenzae type B and Streptococcus pneumonia e is incomplete or unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Introduction of the Haemophilus influenzae type B and Streptococcus pneumoniae vaccines has led to a dramatic reduction in childhood bacterial meningitis 42 . The most recent AAP guideline on the topic does not recommend the routine performance of a lumbar puncture on all children with a simple febrile seizure 2 .…”
Section: Discussionmentioning
confidence: 99%
“…Previous relative studies on the H. influenzae type b epidemiology during the pre- and post-vaccination era in Greece, conducted in the paediatric population in the area of Athens and Crete, reported an incidence of 12.0/100,000 population [ 24 ], with meningitis accounting for 69% of the cases. Hib vaccination was introduced in Greece in 1992 and led to a limitation of meningitis cases [ 25 , 26 , 27 ]. During the same period, a study by Kofteridis et al reported high percentage (58%) of invasive disease of lower respiratory tract due to NTHi [ 28 ].…”
Section: Discussionmentioning
confidence: 99%